x(x-3)=28

Apply the distributive property.

x⋅x+x⋅-3=28

Simplify the expression.

Multiply x by x.

x2+x⋅-3=28

Move -3 to the left of x.

x2-3x=28

x2-3x=28

x2-3x=28

Move 28 to the left side of the equation by subtracting it from both sides.

x2-3x-28=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -28 and whose sum is -3.

-7,4

Write the factored form using these integers.

(x-7)(x+4)=0

(x-7)(x+4)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-7=0

x+4=0

Set the first factor equal to 0.

x-7=0

Add 7 to both sides of the equation.

x=7

x=7

Set the next factor equal to 0.

x+4=0

Subtract 4 from both sides of the equation.

x=-4

x=-4

The final solution is all the values that make (x-7)(x+4)=0 true.

x=7,-4

Solve using the Square Root Property x(x-3)=28